Aspek Perpajakan Biaya Komisi Reasuransi: Studi Kasus Sengketa Pajak Penghasilan Pasal 23 atas Komisi Reasuransi Pada PT X - Pratama, Sonni Cipta (Owner : Riset dan Jurnal Akuntansi, 2024)
Reinsurance commission fees are costs that are inseparable from the reinsurance business with a fairly large cost composition, including the reinsurance business carried out by PT X. Through the withholding tax mechanism in the Indonesian tax system which is regulated in Article 23 of the Income Tax Law, DJP imposes PPh article 23 on reinsurance commissions through a tax audit process, giving rise to a tax dispute between DJP and PT X. This research is a case study with a qualitative method which aims to analyze the tax aspects of reinsurance commission fees through tax disputes faced by PT X, by looking at the substance of reinsurance commission fees through the process of recording and implementing taxation, chronology of tax disputes, company tax management in dealing with disputes , and analysis of expert opinions, to solve the problems faced by PT X in determining whether the reinsurance commission is an object of Income Tax Article 23 or not an object of Income Tax Article 23. This research also aims to find a solution so that tax disputes over reinsurance commission fees do not occur repeatedly in the future. The results of this research show that the reinsurance commission is not an object of PPh Article 23 by looking at the substance of the transaction, as well as the dispute result decision won by PT X for a consecutive five year dispute period which gives permanent legal force to the reinsurance commission case. This indicates that DJP must be more open in understanding the company's business model and business processes, and that DJP field officers must be more careful in implementing tax regulations appropriately.